Approximations to the t distribution - Zogheib, Bashar (2015)
In this paper, a few formulas are found to approximate the t cumulative distribution function. The formulas found in [5] to approximate the normal distributions are used to get good approximations for t. The derived formulas give good approximation for degrees of freedom greater than 3 and if the exact probabilities are less than 0.9.